1979
DOI: 10.1111/j.1440-1681.1979.tb00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vaccination of mice and rats with Haemophilus influenzae and bordetella pertussis as models of atopy

Abstract: 1. Rats and mice were vaccinated with Haemophilus influenzae in different vaccination schedules whereafter blood eosinophils were counted. In rats a single vaccination resulted in a dose-dependent effect on the blood eosinophil count in a pattern comparable with that after Bordetella pertussis vaccination. In a long-term vaccination schedule (five times a week for 5 weeks) rats developed a constant eosinophilia. In mice a single vaccination resulted in an eosinopenia of a consistent pattern which differed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…'atopic dogs' or the anaphylactic state (Middleton, 1972;Patterson, 1974), hypothalamic lesions (Macris et al, 1970) and impairment of /3-adrenoceptor function (Townley et al, 1967) whereas vaccination with B. pertussis has also been used as a model of atopy (Szentivanyi, 1968). However, Terpstra et al (1979) described vaccination with H. influenzae as a better model for human atopy because H. influenzae is one of the most common bacteria found in the lower respiratory tract of patients with chronic asthmatic bronchitis (see Hirschmann and Everett, 1979;Van der Zwan, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'atopic dogs' or the anaphylactic state (Middleton, 1972;Patterson, 1974), hypothalamic lesions (Macris et al, 1970) and impairment of /3-adrenoceptor function (Townley et al, 1967) whereas vaccination with B. pertussis has also been used as a model of atopy (Szentivanyi, 1968). However, Terpstra et al (1979) described vaccination with H. influenzae as a better model for human atopy because H. influenzae is one of the most common bacteria found in the lower respiratory tract of patients with chronic asthmatic bronchitis (see Hirschmann and Everett, 1979;Van der Zwan, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Terpstra et al (1979) showed that in rats 4 days after vaccination, both lung and plasma histamine levels were increased and mast cell histamine content was elevated so it seems logical that more histamine would also be released after ovalbumin shock.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal administration to rodents of killed Gram-negative bacteria like Bordetella pertussis and Haemophilus influenzae or the common cell-wall component endotoxin has been shown to be a valid animal model for atopy in which non-specific airway hyperreactivity occurs, together with other criteria for atopy like eosinophilia and enhanced IgE anti-'Author for correspondence. body production (Szentivanyi, 1968;Terpstra et al, 1979;Nijkamp & Schreurs, 1984). Furthermore, we showed previously that an imbalance between the cholinergic bronchoconstrictorand the fl-adrenergic bronchodilator systems in guinea-pig isolated trachea occurred, four days after i.p.…”
Section: Introductionmentioning
confidence: 99%
“…Sus pensions of noncapsulated H. influenzae organ isms were obtained from the Department of Mi crobiology of the Academic Hospital Utrecht. The stock suspension contained 5,000 million killed cells per milliliter and was injected intraperito-neally in a volume of 0.1 ml, representing a dose inducing considerable effects on /5-adrenoceptor activity 4 days after vaccination [25,26] Rat peritoneal mast cells were isolated accord ing to the procedure described by Sullivan et at. [22], with the exception that heparin was omitted from the mast cell medium.…”
Section: Methodsmentioning
confidence: 99%